If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + -32 = 3f + -12 Reorder the terms: -32 + f = 3f + -12 Reorder the terms: -32 + f = -12 + 3f Solving -32 + f = -12 + 3f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-3f' to each side of the equation. -32 + f + -3f = -12 + 3f + -3f Combine like terms: f + -3f = -2f -32 + -2f = -12 + 3f + -3f Combine like terms: 3f + -3f = 0 -32 + -2f = -12 + 0 -32 + -2f = -12 Add '32' to each side of the equation. -32 + 32 + -2f = -12 + 32 Combine like terms: -32 + 32 = 0 0 + -2f = -12 + 32 -2f = -12 + 32 Combine like terms: -12 + 32 = 20 -2f = 20 Divide each side by '-2'. f = -10 Simplifying f = -10
| q^2-11q+28= | | f+32=3f+25 | | 7n-5n-(-12)-3n=-11 | | 18-2M=4 | | 9x-5(2x+1)=-28 | | 0.14+0.23(6)=c | | 18a+2a-11a-9a+2a=14 | | 6(a-b)=36 | | 73.426+what=1.39 | | 21-=-8 | | 3+65x=52x+15 | | 3t+6t-8t=11 | | (2x+25)+(x+5)=180 | | -37=-91 | | -8x-2y=2 | | 2x+8=3(x+9) | | 13s-11s+2s-4s+s=17 | | 5n+18d= | | 5x+2(x-2)=74 | | 15x+=120 | | 8h-28=52 | | f-32=3f-12 | | 10g-4g-6g+g=20 | | v(x)=x(12-2x)(18-2x) | | -13n+14=-12n-5 | | f-32=3f-1# | | 5x+4x+3x=4x+2 | | 5u-3u=20 | | 3k-10=40 | | 19+3x=6x-2 | | Z=cbforg | | q-5=3q+25 |